Immunotherapy revolutionizing brain metastatic cancer treatment: personalized strategies for transformative outcomes - Li, Ting; Sun, Shichen; Li, Yubing; Zhang, Yanyu; Wei, Linlin (Frontiers in Immunology, 2024)
Brain metastatic cancer poses a significant clinical challenge, with limited treatment options and poor prognosis for patients. In recent years, immunotherapy has emerged as a promising strategy for addressing brain metastases, offering distinct advantages over conventional treatments. This review explores the evolving landscape of tumor immunotherapy in the context of brain metastatic cancer, focusing on the intricate interplay between the tumor microenvironment (TME) and immunotherapeutic approaches. By elucidating the complex interactions within the TME, including the role of immune cells, cytokines, and extracellular matrix components, this review highlights the potential of immunotherapy to reshape the treatment paradigm for brain metastases. Leveraging immune checkpoint inhibitors, cellular immunotherapies, and personalized treatment strategies, immunotherapy holds promise in overcoming the challenges posed by the blood-brain barrier and immunosuppressive microenvironment of brain metastases. Through a comprehensive analysis of current research findings and future directions, this review underscores the transformative impact of immunotherapy on the management of brain metastatic cancer, offering new insights and opportunities for personalized and precise therapeutic interventions.